Ischemic stroke caused by large-artery atherosclerosis: a red flag for subclinical coronary artery disease - de Araújo, Ana Luíza Vieira; Santos, Raul D.; Bittencourt, Marcio Sommer; Dantas, Roberto Nery; Oshiro, Carlos André; Nomura, Cesar Higa; Bor-Seng-Shu, Edson; Oliveira, Marcelo de Lima; Leite, Claudia da Costa; Martin, Maria da Graça Morais; Alves, Maramelia Miranda; Silva, Gisele Sampaio; et al. (Frontiers in Neurology, 2023)
Background The coronary calcium score (CAC) measured on chest computerized tomography is a risk marker of cardiac events and mortality. We compared CAC scores in two multiethnic groups without symptomatic coronary artery disease: subjects in the chronic phase after stroke or transient ischemic attack and at least one symptomatic stenosis ≥50% in the carotid or vertebrobasilar territories (Groupathero) and a control group (Groupcontrol). Methods In this cross-sectional study, Groupathero included two subgroups: GroupExtraorIntra, with stenoses in either cervical or intracranial arteries, and GroupExtra&Intra, with stenoses in at least one cervical and one intracranial artery. Groupcontrol had no history of prior stroke/transient ischemic attacks and no stenoses ≥50% in cervical or intracranial arteries. Age and sex were comparable in all groups. Frequencies of CAC ≥100 and CAC > 0 were compared between Groupathero and Groupcontrol, as well as between GroupExtraorIntr, GroupExtra&Intra, and Groupcontrol, with bivariate logistic regressions. Multivariate analyses were also performed. Results A total of 120 patients were included: 80 in Groupathero and 40 in Groupcontrol. CAC >0 was significantly more frequent in Groupathero (85%) than Groupcontrol (OR, 4.19; 1.74–10.07; p = 0.001). Rates of CAC ≥100 were not significantly different between Groupathero and Groupcontrol but were significantly greater in GroupExtra&Intra (n = 13) when compared to Groupcontrol (OR 4.67; 1.21–18.04; p = 0.025). In multivariate-adjusted analyses, “Groupathero” and “GroupExtra&Intra” were significantly associated with CAC. Conclusion The frequency of coronary calcification was higher in subjects with stroke caused by large-artery atherosclerosis than in controls.